Analysis of Postoperative Remodeling Characteristics after Modular Inner Branched Stent-Graft Treatment of Aortic Arch Pathologies Using Computational Fluid Dynamics - Fen Li; Yating Zhu; Hui Song; Hongpeng Zhang; Lingfeng Chen; Wei Guo (Bioengineering, 2023)
The modular inner branched stent-graft (MIBSG), a novel interventional therapy, has demonstrated good effects in the endovascular treatment of aortic arch pathologies, especially those involving the supra-aortic branches. Nevertheless, the long-term efficacy of the MIBSG and in-depth quantitative evaluation of postoperative outcomes remain to be examined. Moreover, the regularity of postoperative vascular remodeling induced by MIBSG implantation has yet to be explored. To address these questions, we constructed four models (normal, preoperative, 1 week postoperative, and 6 months postoperative) based on a single patient case to perform computational fluid dynamics simulations. The morphological and hemodynamic characteristics, including the velocity profile, flow rate distribution, and hemodynamic parameter distribution (wall shear stress and its derivative parameters), were investigated. After MIBSG implantation, the morphology of the supra-aortic branches changed significantly, and the branch point moved forward to the proximal ascending aorta. Moreover, the curvature radius of the aortic arch axis continued to change. These changes in morphology altered the characteristics of the flow field and wall shear stress distribution. As a result, the local forces exerted on the vessel wall by the blood led to vessel remodeling. This study provides insight into the vascular remodeling process after MIBSG implantation, which occurs as a result of the interplay between vascular morphological characteristics and blood flow characteristics.